Primary Hairy Cell Leukemia/Lymphoma of the Breast: A Case Report and Review of the Literature - Monika Pilichowska; Ahmad Shariftabrizi; Ian Mukand-Cerro; Kenneth Miller (Case Reports in Pathology)
Hairy cell leukemia/lymphoma (HCL) is a rare B-cell neoplasm primarily involving spleen, bone marrow, and blood. However, other sites of primary involvement do occur and can present a diagnostic and therapeutic challenge. We present an unusual case of HCL involving predominantly the breast that was diagnosed as an incidental finding during an elective reduction mammoplasty in an otherwise healthy asymptomatic woman. Bone marrow performed for staging revealed limited involvement by HCL. Notably, there was no splenomegaly and/or involvement of other extramedullary sites. The peripheral blood revealed minimal involvement detected by flow cytometry. Extensive immunohistochemical studies supported by positive BRAF V600E mutational status confirmed the diagnosis of HCL. The patient remains asymptomatic without treatment one year following the diagnosis. This is the first case of a well-documented HCL presenting primarily in the breast in an asymptomatic patient. We review the literature on extramedullary, extrasplenic involvement by HCL and discuss the diagnostic challenges as well as the utility of immunohistochemistry and molecular studies in the diagnosis of atypical presentations of HCL.